1988
DOI: 10.1126/science.3422517
|View full text |Cite
|
Sign up to set email alerts
|

Mesoderm Induction in Amphibians: the Role of TGF-β2-Like Factors

Abstract: Mesoderm induction in the amphibian embryo can be studied by exposing animal region explants (destined to become ectoderm) to appropriate stimuli and assaying the appearance of mesodermal products like alpha-actin messenger RNA. Transforming growth factor beta 2 (TGF-beta 2), but not TGF-beta 1, was active in alpha-actin induction, while addition of fibroblast growth factor had a small synergistic effect. Medium conditioned by Xenopus XTC cells (XTC-CM), known to have powerful mesoderm-inducing activity, was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(127 citation statements)
references
References 30 publications
2
125
0
Order By: Relevance
“…In the mouse embryo, TGF-/32 mRNA and its protein were found primarily in mesoderm-derived organs [6]. Rosa et al reported that TGF-/32-like activity augments mesoderm induction [26]. TGF-^1 is also important for the development of mesoderm-derived organs [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse embryo, TGF-/32 mRNA and its protein were found primarily in mesoderm-derived organs [6]. Rosa et al reported that TGF-/32-like activity augments mesoderm induction [26]. TGF-^1 is also important for the development of mesoderm-derived organs [27].…”
Section: Discussionmentioning
confidence: 99%
“…Some induction events occur by exchange of diffusible signals or morphogens, as shown for TGF p-like molecules and activin (Rosa et al, 1988;Smith, 1987). Others may occur only by direct cell-cell interaction as seen in "bride of sevenless'' interactions in Drosophila eyes (Kramer et al, 1991).…”
Section: Cell Surface Modulation and The Control And Dissociation Of mentioning
confidence: 99%
“…gene expression (Gurdon, 1987;Rosa et al, 1988;Smith, 1987), the isolation of cell adhesion molecules (Edelman and Crossin, 19911, new knowledge of the mode of action of homeotic genes (Gehring, 1987;Gaunt et al, 1988), and increasing insight into the molecular factors governing cell division, cell shape and motion, and cell death (Nurse, 1991;Borneus, 1991;Bock and O'Connor, 1987). It is not too early in any attempt to understand morphogenesis to ask how all of these matters relate to one another.…”
Section: York 10021mentioning
confidence: 99%
“…They were treated with FGF, activin, or cycloheximide according to Rosa et al (1988) and Rosa (1989). We have used the following factor concentrations: 50 pM activin; 100 ng/ml of bFGF.…”
Section: Induction Experimentsmentioning
confidence: 99%